Enhancing mothers’ understanding of sanitation and nutrition for stunting prevention through a participatory approach in Palembang - Annisa Kemala Tasya; Delia Yusfarani; Andi Saputra; Siti Soleha; Anita Restu Puji Raharjeng; Fitri Juneli; Vega Putri Masdalena; Gusti Aryanti; Naomi Puspita Dewi; Nur Azizah (Universitas Ahmad Dahlan, 2025)
Stunting in Indonesia is closely linked to inadequate sanitation and maternal health literacy. This community service program aimed to improve mothers’ knowledge and sanitation practices for stunting prevention through a Participatory Action Research (PAR) approach in Palembang. The program involved 39 mothers of stunted children across four public health centers. Evaluation was conducted using pre–post KAP questionnaires, household observations, and environmental measurements. The results showed that 82% of participants improved their knowledge scores compared to baseline, with average scores increasing from low to good levels. Observable behavioral changes included proper handwashing, improved waste management, safer water storage, and better home ventilation. Coliform contamination in drinking water decreased from 58.2 to 5.13 CFU/100 mL, indicating a positive improvement trend, although not yet meeting WHO standards. The formation of the “Ibu Peduli Sanitasi” group strengthened sustainability through peer education and community monitoring. This program demonstrates that participatory community empowerment effectively enhances maternal capacity and promotes sustainable sanitation behavior in stunting prevention